SURGICAL TREATMENT OF CEREBRAL PERIVENTRICULAR GLIOMAS: CONSEQUENCES OF THE OF PORENCEPHALY FORMATION AND FEATURES OF SURGICAL WOUND CLOSURE - Rozumenko, Artem; Kliuchka, Valentyn; Rozumenko, Volodymir; Daschakovskiy, Andriy (The Ukrainian Scientific Medical Youth Journal, 2021)
The paper presents the experience of surgical treatment of patients with cerebral periventricular gliomas. The factors influencing on the results of treatment in the short postoper- ative period were analyzed. Methods of surgical wound closure preventing the development of ce- rebrospinal fluid disorders due to the formation of porencephaly were proposed.